Oxidative Stress, Inflammation, and Activators of Mitochondrial Biogenesis: Tempol Targets in the Diaphragm Muscle of Exercise Trained-mdx Mice - Silva, Heloina Nathalliê Mariano da; Covatti, Caroline; Rocha, Guilherme Luiz da; Mizobuti, Daniela Sayuri; Mâncio, Rafael Dias; Hermes, Túlio de Almeida; Kido, Larissa Akemi; Cagnon, Valéria Helena Alves; Pereira, Elaine Cristina Leite; Minatel, Elaine (Frontiers in Physiology, 2021)
The mdx mouse phenotype aggravated by chronic exercise on a treadmill, makes this murine model more reliable for the study of muscular dystrophy. Thus, to better assess the Tempol effect on dystrophic pathways, the analyses in this study were performed in blood samples and diaphragm muscle from treadmill trained adult (7-11-weeks old) mdx animals. The mdx mice were divided into three groups: mdxSed, sedentary controls (n=28); mdxEx, exercise-trained animals (n=28); and mdxEx+T, exercise-trained animals with Tempol treatment (n=28). The results demonstrated that Tempol treatment promoted muscle strength gain; prevented muscle damage; reduced the inflammatory process, oxidative stress and angiogenesis regulator; and up regulated the activators of mitochondrial biogenesis. The main new findings of this study are that Tempol reduced the NF-κB and increased the PGC1-α and PPARδ levels in the exercise-trained-mdx mice, which are probably related to the ability of this antioxidant to scavenge excessive ROS. These results reinforce the use of Tempol as a potential therapeutic strategy in DMD.